Effects of cardiac resynchronization therapy after inferior myocardial infarction on secondary mitral regurgitation and mitral valve geometry. Issue 2 (16th January 2018) - Mihos, Christos G.; Yucel, Evin; Capoulade, Romain; Orencole, Mary P.; Upadhyay, Gaurav A.; Santana, Orlando; Singh, Jagmeet P.; Picard, Michael H.
Abstract: Background: The effects of cardiac resynchronization therapy (CRT) on secondary mitral regurgitation (MR), and mitral valve (MV) and left ventricular (LV) geometry, in patients with prior inferior myocardial infarction is not clearly defined. We assessed these outcomes utilizing two‐dimensional echocardiography, and analyzed echocardiographic geometric variables that may correlate with follow‐up MR severity. Methods: Between 2009 and 2012, 229 CRT were implanted. Twenty‐two had prior inferior myocardial infarction, ≥mild MR at baseline, and serial echocardiography. A left bundle branch block was present in 12 (54.5%) patients. The pre‐CRT and follow‐up echocardiograms were analyzed for: (1) MR severity; (2) MV and LV geometry; and (3) LV remodeling. Results: The median follow‐up time was 2.2 years (interquartile range, 0.7–4). In 16 patients without an inferior myocardial scar, there was a reduction in MR jet area/left atrial area ratio (33.2% vs 25.8%; P = 0.06) and MR grade (2.3 vs 1.8; P = 0.05), and an increased LV ejection fraction (26.1% vs 30.9%; P = 0.04) and end‐systolic posterior ventricular sulcus‐anterolateral papillary muscle angle (133.9 vs 143.9 degrees; P = 0.01). In six patients with scar, there was no change in LV or MR parameters. Regression analysis revealed linear associations between baseline MV tenting height (r = 0.57; P = 0.006), LV end‐diastolic diameter index (r = 0.5; P = 0.02), mitral septolateral annular diameter (r = 0.48; P = 0.03), and MV tenting area (r = 0.46; P = 0.03), with follow‐up MR jet area/left atrial area ratio. Conclusions: In patients with prior inferior myocardial infarction and no scar, CRT is associated with decreased MR severity, and improved papillary muscle alignment and LV systolic function at follow‐up.